Does Environmental Performance In Green Accounting Affect Profitability? - Novrida Qudsi Lutfillah; Thea Samantha Amadea (Universitas Muhammadiyah Jakarta, 2022)
This study aims to examine the effect of implementing Green Accounting as measured by Environmental Performance and Environmental Disclosure on Profitability. The t test was used as the method of analysis. The research sample is additional companies listed on the Indonesia Stock Exchange in 2017-2020. The results showed that environmental performance had no effect on profitability, while environmental disclosure had an effect on the profitability of mining companies. The demands on environmental performance made by the company are more directed at companies with large sizes, not to companies with high profitability. Furthermore, environmental disclosure is a means to meet the expectations and needs of stakeholders who want to learn more about the company's environmental performance through annual reports. If the ROA value is not in prime condition, it will have an impact on the company's environmental disclosure.